Water and a protic ionic liquid acted as refolding additives for chemically denatured enzymes - Attri, Pankaj; Venkatesu, P.; Kumar, Anil (Organic & Biomolecular Chemistry, 2012)
In this communication, we present the ability of water and a protic ionic liquid, triethyl ammonium phosphate (TEAP) to act as refolding additives for the urea-induced chemical denaturated state of the two enzymes, alpha-chymotrypsin and succinylated Con A. We show that the enzymatic activity is regained and in certain circumstances enhanced.